A Characterization of the Humoral Immune Response to Human Endogenous Retroviruses and Mycobacterium paratuberculosis in Crohn’s Disease - Alishba Fayyaz; Luigi Cugia; Marta Noli; Somaye Jasemi; Elena Rita Simula; Leonardo A. Sechi (Pathogens)
Crohn’s disease (CD) is a multifactorial polygenic inflammatory bowel disease linked to aberrant immune response. Mycobacterium paratuberculosis (MAP) has been associated with CD; however, detecting MAP in CD tissues remains highly challenging. Recently, Human Endogenous Retroviruses (HERVs) differential gene expression has been reported in CD, but little is known about the involvement of MAP and HERVs in CD pathology. This study aimed to characterize the humoral response against HERV-K, HERV-W, and MAP antigens using an indirect ELISA in plasma samples from CD patients and age- and gender-matched healthy controls (HCs). We observed a significant antibody response against HERV-K and HERV-W epitopes in CD patients in comparison to MAP epitopes, as well as a higher overall antibody response in patients compared to HCs. This study is the first to report the presence of humoral immune response against HERVs antigens in CD. Considering the pro-inflammatory nature of CD, HERVs may contribute to the development or progression of disease in genetically predisposed individuals. However, further research is needed to better understand the complex role of HERVs in CD.